Perbuatan Melawan Hukum Oleh Badan Pertanahan Nasional Terkait Sertifikat Pengganti Hak Milik Atas Tanah - Prakasa, Nugraha Medica; Maulidiana, Lina; Abadi, Nikmat; Renaldy, Rendy (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Land registration is a government task carried out in order to ensure legal certainty in the land sector (a "Rechts Kadastre" or "Legal Cadastre"). The purpose of land registration is stated in Article 3 of Government Regulation Number 24 of 1997. To achieve this orderly administration, every plot of land and apartment unit including transfer, encumbrance and write-off must be registered in Government Regulation Number 24 of 1997. Article 1 paragraph (20) states: "Certificate is a certificate of proof of rights as intended in Article 19 paragraph (2) letter c UUPA for land rights, management rights, waqf land, ownership rights to apartment units and mortgage rights, each of which has been recorded in the relevant land book. The method used in this research is a normative approach and a Socio Legal approach which originates from collecting data obtained from primary data and secondary data, then analyzed using qualitative analysis methods. The results of this research answer that the form of unlawful action by the National Land Agency regarding land ownership certificates based on Decision Number 169/Pdt.G/2022/PN.Tjk is not carrying out community requests regarding Government Regulation Number 24 of 1997 concerning Land Registration Article 57 paragraph (1) which explains that at the request of the right holder a new certificate is issued as a replacement for a certificate that is damaged, lost, still uses a blank certificate that is no longer used or that was not handed over to the auction buyer in an execution auction. Meanwhile, the analysis of the judge's considerations regarding unlawful acts by the National Land Agency regarding certificates of ownership of land based on Decision Number 169/Pdt.G/2022/PN.Tjk is from a normative aspect because Certificate of Ownership Number 926/Kd, issued on May 9 1977, is located in Sukarame Village, Kedaton District, Bandar Lampung City with Measurement Letter Number 2931/1977 dated 7 February 1977 with an area of 8,400 (eight thousand four hundred) square meters in the name of Purwanto, which is a legal product of State Administrative Officials and is owned by the Plaintiff based on a gift from his parents.